2001
DOI: 10.1073/pnas.121172898
|View full text |Cite
|
Sign up to set email alerts
|

Antigen presentation subverted: Structure of the human cytomegalovirus protein US2 bound to the class I molecule HLA-A2

Abstract: Many persistent viruses have evolved the ability to subvert MHC class I antigen presentation. Indeed, human cytomegalovirus (HCMV) encodes at least four proteins that down-regulate cellsurface expression of class I. The HCMV unique short (US)2 glycoprotein binds newly synthesized class I molecules within the endoplasmic reticulum (ER) and subsequently targets them for proteasomal degradation. We report the crystal structure of US2 bound to the HLA-A2͞Tax peptide complex. US2 associates with HLA-A2 at the junct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
134
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(141 citation statements)
references
References 51 publications
6
134
1
Order By: Relevance
“…Likewise, deletion of the N-terminal 90 residues also reduces the amount of TAP that coimmunoprecipitates with HCMV US6, suggesting that this region also stabilizes the interaction between HCMV US6 and TAP. Although the three-dimensional structure of HCMV US6 is unknown, by comparison with HCMV US2, whose structure has been solved, US6 has been proposed to have an immunoglobulin fold (13). Immunoglobulin domains often mediate protein-protein interactions, and it is conceivable that residues 89 to 108 may form a TAP binding surface analogous to the MHC class I binding surface formed by US2.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, deletion of the N-terminal 90 residues also reduces the amount of TAP that coimmunoprecipitates with HCMV US6, suggesting that this region also stabilizes the interaction between HCMV US6 and TAP. Although the three-dimensional structure of HCMV US6 is unknown, by comparison with HCMV US2, whose structure has been solved, US6 has been proposed to have an immunoglobulin fold (13). Immunoglobulin domains often mediate protein-protein interactions, and it is conceivable that residues 89 to 108 may form a TAP binding surface analogous to the MHC class I binding surface formed by US2.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the α2 helix domain residues of RAE1γ, including Lys154, Tyr155, and Glu159, form an important contact site for both m152 and NKG2D. (33), that of the MHC-I-like UL18 with the Ig-like LIR-1 (34), and that of the Ig-like UL16 with the MHC-I-like hNKG2D ligand MICB (29). In all these complexes, the viral molecule exploits a different aspect of the host cell's ligand for interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Further analyses indicated that ER lumenal domain of HCMV US2 is required for physiologically interaction with the α3 domain of hCD1d. Previous observation also demonstrated that ER lumenal domain of HCMV US2 is the major binding site for both MHC class Ia and class II molecules (Chevalier et al, 2002;Gewurz et al, 2001). Although hCD1d, heavy chain of MHC class Ia (HLA-A2) and MHC class II molecules (HLA-DM, HLA-DR) share only 25 to 30% of amino acid identity, ER lumenal domain of HCMV US2 still can bind to these molecules.…”
Section: Discussionmentioning
confidence: 95%
“…In addition, we identified the α3 domain of hCD1d as the major binding site of HCMV US2. Previous observation indicated that HCMV US2 binding site of heavy chain of MHC class Ia molecule (HLA-A2) is located mainly in the α3 domain of the heavy chain, which is remote from the peptide binding motif (Gewurz et al, 2001). Thus, hCD1d and MHC class Ia molecule also share the region that interacts with HCMV US2.…”
Section: Discussionmentioning
confidence: 99%